2021
DOI: 10.1007/jhep12(2021)047
|View full text |Cite
|
Sign up to set email alerts
|

Searching for heavy leptoquarks at a muon collider

Abstract: The LHCb Collaboration recently gave an update on testing lepton flavour universality with B+→ K+ℓ+ℓ−, in which a 3.1 standard deviations from the standard model prediction was observed. The g-2 experiment also reports a 3.3 standard deviations from the standard model on muon anomalous magnetic moment measurement. These deviations could be explained by introducing new particles including leptoquarks. In this paper, we show the possibility to search for heavy spin-1 leptoquarks at a future TeV scale muon collid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 59 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…The reason for choosing diverse benchmark models is to broadly cover the BSM space. There have already been several prospect studies for some of these models at the FCChh [42][43][44][45][46][47][48], MuC [48][49][50][51][52][53][54][55], CLIC [56] and HL(HE)-LHC [42,43,57,58]. Throughout the paper we comment on the similarities and differences between our study and some of the previous ones.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The reason for choosing diverse benchmark models is to broadly cover the BSM space. There have already been several prospect studies for some of these models at the FCChh [42][43][44][45][46][47][48], MuC [48][49][50][51][52][53][54][55], CLIC [56] and HL(HE)-LHC [42,43,57,58]. Throughout the paper we comment on the similarities and differences between our study and some of the previous ones.…”
Section: Introductionmentioning
confidence: 58%
“…In Ref. [52] it was shown that studying the rapidity distribution of the final state jets could provide additional handles to increase the signal to background ratio for leptoquarks.…”
Section: Di-jet: µμ→ Jjmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that detailed muon collider sensitivity projections for the BSM candidates in Figure 3 have not been performed yet. In general, a relatively limited literature exists on direct new physics searches at the MuC [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. More studies would be desirable also to offer targets to the design of the detector.…”
Section: Direct Reachmentioning
confidence: 99%
“…Interestingly enough, we found that, based on a set of high-intensity electron beam and liquid hydrogen target-both have been used to search for sub-GeV dark vector bosons [83][84][85][86]-and taking into account the most stringent constraints on the corresponding LQ interactions from other processes, very promising event rates can be expected for both the scattering processes in some specific LQ models [82]. Motivated by such a promising prospect of the LQ searches at the low-energy scattering processes (as well as the tenacious hunting for the LQs at the Large Hadron Collider (LHC) [87][88][89][90][91][92][93][94] and other future facilities [95,96]), we will address another interesting question: can the different LQs be systematically disentangled from each other through the low-energy FCNC scattering processes?…”
Section: Introductionmentioning
confidence: 99%